Evaluation of bone mineral density (BMD) and the effect of type of factor replacement therapy on BMD in children with hemophilia: A single-center observational study - Govind R. Patel; Renu Saxena; Sadhna Aggarwal; Manoranjan Mahapatra (Elsevier, 2022)
Background: The higher life expectancy in patients with hemophilia (PWH) due to better care has increased the incidence of age-related complications such as osteoporosis. This study was conducted to assess the bone mineral density (BMD) and its correlation with determinants of hemophilic arthropathy and to evaluate the effect of type of factor replacement therapy on BMD in Indian hemophilic children. Methods: This study was conducted on 39 hemophilic children and 40 healthy controls. Total range-of-motion (ROM) score was calculated for major affected joints and BMD was measured by dual-energy x-ray absorptiometry at baseline and repeated at follow-up after 6 months period during which all patients received either prophylaxis or on-demand therapy. Results: BMD and BMD Z-scores were significantly reduced in hemophiliacs as compared to controls (p < 0.05). The prevalence of low BMD in hemophiliacs ranged from 30.8 to 41% at various sites. A signiﬁcant correlation was found between BMD Z-score and episodes of joint bleed, number of target joints, and total joint ROM score (p < 0.05). BMD Z-score showed a significant difference between the prophylaxis group and on-demand therapy group at baseline, and a significant increase in BMD Z-score was observed among patients in prophylaxis group at follow-up after 6 months compared to baseline (p < 0.05) but not among patients in on-demand therapy group. Conclusions: Hemophilic children showed reduced BMD that correlated with hemophilic arthropathy. Prophylaxis, as compared to on-demand therapy, markedly decreased hemarthrosis and consequent immobilization, and thereby retarded the progression of bone mineral loss and improved BMD in these patients.